ANALISIS SWOT PADA USAHA RUMAH MAKAN NASIONAL - Zebua, Nofita Rupawan (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The aim of this research is to find out effective alternative strategies that can be used by national restaurant businesses based on their external and internal factors. This research is qualitative research with a descriptive approach. The data sources in this research are business owners, employees and customers in national restaurant businesses. The data collection techniques used were observation, interviews, documentation, literature study, questionnaires, with data analysis techniques namely SWOT, IFAS and EFAS analysis techniques, SWOT diagrams and SWOT matrices. The results of the research found a total IFAS score of 1.05 and a total EFAS score of -0.54 which can be concluded that the business position is in quadrant II, namely having strengths and facing threats. In this position the National restaurant business supports a diversification strategy, namely a strategy that utilizes existing strengths. Yes, the alternative strategy is optimizing operational activities, building relationships with suppliers improve product quality.